Meningkatkan Pencegahan daripada Pengobatan Terhadap Covid-19 Kepada Masyarakat di Desa Santong Mulia dan Pencegahan Pernikahan Usia Dini - Nanik Sulistiani (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2022)
The Covid-19 virus has lasted until now. As long as the pandemic continues, it takes a sense of caring from the community to work together in an effort to increase prevention in reducing the risk of being exposed to Covid-19. These efforts can be in the form of always obeying health protocols such as maintaining distance, washing hands, using masks, using hand sanitizers, and maintaining environmental cleanliness, and obeying government regulations to participate in vaccinations and comply with existing PPKM. from the Covid-19 virus. During this pandemic, schools are conducted online so the learning process is less effective, which triggers children to feel bored and choose to marry at an early age. In this case, teenagers need to be given education regarding the impact of early marriage, and the risks that will be faced if married at an insufficient age. Therefore, KKP DR collaborated with the North Lombok Genre Forum to help provide education related to this in the Socialization Event on Prevention of Early Childhood Marriage in the Santong Mulia Village Office Hall which is targeted at teenagers under the age of 19.